2017
DOI: 10.1016/j.schres.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Brain bioenergetics and redox state measured by 31 P magnetic resonance spectroscopy in unaffected siblings of patients with psychotic disorders

Abstract: Background Brain bioenergetic anomalies and redox dysregulation have been implicated in the pathophysiology of psychotic disorders. The present study examined brain energy-related metabolites and the balance between nicotinamide adenine dinucleotide metabolites (oxidized NAD+ and reduced NADH) using 31P-magnetic resonance spectroscopy (31P-MRS) in unaffected siblings, compared to first episode psychosis (FEP) patients and healthy controls. Methods 21 unaffected siblings, 32 FEP patients (including schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…31 P MRS at high magnetic field is a powerful non-invasive method to measure metabolic and physiological parameters in the brain ( 30 ) including important 31 P-metabolites involved in brain energy metabolism (PCr, Pi, ATP) and membrane synthesis/degradation (PC, PE, GPC, GPE), metabolic fluxes (k f, CK and k f, ATPase ), intra-/extra-cellular pH, free Mg 2+ concentration, as well as most recently the redox state (NAD + /NADH) ( 11 13 ). To measure the aforementioned metabolic and physiological parameters with a focus on redox state and forward rate constants of CK(k f, CK ) and ATPase(k f, ATPase ), a scanning protocol of the occipital region was established in a pilot test-retest study in 6 healthy volunteers (method section and Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 P MRS at high magnetic field is a powerful non-invasive method to measure metabolic and physiological parameters in the brain ( 30 ) including important 31 P-metabolites involved in brain energy metabolism (PCr, Pi, ATP) and membrane synthesis/degradation (PC, PE, GPC, GPE), metabolic fluxes (k f, CK and k f, ATPase ), intra-/extra-cellular pH, free Mg 2+ concentration, as well as most recently the redox state (NAD + /NADH) ( 11 13 ). To measure the aforementioned metabolic and physiological parameters with a focus on redox state and forward rate constants of CK(k f, CK ) and ATPase(k f, ATPase ), a scanning protocol of the occipital region was established in a pilot test-retest study in 6 healthy volunteers (method section and Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
“…[γ-ATP] was assumed to be 3 mM in the human occipital lobe and used as an internal concentration reference. To be comparable with literatures, NAD + , NADH, and UDPG concentrations were calculated assuming [α-ATP] of 2.8 mM ( 12 , 13 ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Dysfunctional energy metabolism and oxidative stress are key pathophysiologic mechanisms in T2DM 51 , and we now also have converging evidence in psychotic disorders for energy metabolism impairment in the brain 57 59 . 31 P magnetic resonance spectroscopy studies have revealed specific bioenergetic abnormalities and redox imbalance in FEP patients and unaffected siblings 60 , 61 . In psychotic and bipolar disorders, recent evidence suggests that obesity and abnormal glucose metabolism are associated with severity of illness, greater number of hospitalizations, suicide attempts, and neurochemical-structural abnormalities 62 65 .…”
Section: Discussionmentioning
confidence: 99%
“… Martins-de-Souza et al (2012) speculated that a reduction in ATP could be due to oxidative stress and that the increased levels of subunits of OXPHOS complexes were compensatory. In fact, ATP reduction and its relation to oxidative stress have been linked not only to depression (detailed below), but also to psychotic disorders (see Chouinard et al, 2017 ), autism ( Rose et al, 2014 ), anxiety ( Kumar and Chanana, 2017 ), Alzheimer’s disease (recently reviewed in Tramutola et al, 2017 ), and Huntington disease ( Quintanilla et al, 2017 ).…”
Section: Oxidative Stressmentioning
confidence: 99%